A clinical study on minimally invasive percutaneous nephrolithotomy combined with ureteral access sheath for the treatment of kidney stones - Liu, Boyang; Kang, Yanjie; Shang, Yafeng (Frontiers in Surgery, 2025)
ObjectiveTo investigate the efficacy and safety of minimally invasive percutaneous nephrolithotomy (MPCNL) combined with ureteral access sheath in the treatment of complex kidney stones.MethodsSeventy patients with complex kidney stones in the author's hospital from June 2022 to December 2023 were randomized. There were 35 cases of minimally invasive percutaneous nephrolithotomy combined with ureteral access sheath and 35 cases of minimally invasive percutaneous nephrolithotomy alone.ResultsCompared to the MPCNL group, the MPCNL + UAS group demonstrated a significantly shorter operative time (55.4 ± 9.2 min vs. 61.5 ± 12.8 min, p = 0.027), significantly lower intraoperative renal pelvic pressure (9.15 ± 4.13 mmHg vs. 11.35 ± 4.21 mmHg, p = 0.031), and a significantly lower incidence of postoperative Clavien complications (p < 0.05); however, there were no significant differences between the groups in postoperative creatinine change, stone clearance rate at 1 day postoperatively, or stone clearance rate at 30 days postoperatively (p > 0.05).ConclusionsMinimally invasive percutaneous nephrolithotomy combined with ureteral access sheath is safe and effective in the treatment of complex kidney stones. Ureteral access sheath can significantly shorten the operation time of minimally invasive PCNL, keep the visual field clear, reduce the pressure of renal pelvis, and reduce the incidence of complications.